Analisis Kemampuan Literasi Siswa Kelas V dalam Menyelesaikan Soal Asesmen Kompetensi Minimum - Tressa Linanda; Deri Hendriawan (Universitas Muhammadiyah Kuningan, 2022)
The National Assessment consists of a Minimum Competency Assessment (AKM), a Character Survey and a Learning Environment Survey. Literacy skills in AKM consist of informational text content and fictional texts by emphasizing students to be able to understand, evaluate, and reflect on texts on questions with the aim of developing individuals to be able to develop themselves optimally as Indonesian citizens. The location of this research was carried out by SD Negeri Lilang with the aim of identifying the reading literacy skills of fifth grade students in solving Minimum Competency Assessment simulation questions. The research approach used is a qualitative approach with content analysis methods. The subjects in this study were the researchers themselves. The object of the research is a simulation test sheet for class V students as many as 30 students. Data collection was carried out in this study using tests, interviews and documentation. The literacy ability of class V students got the results that from 30 students, as many as 20 students or 66.67% were in moderate ability.